Wakalah Bil Ujrah Agreement in Compilation of Sharia Economic Law, DSN-MUI Fatwa and Qanun - Muhammad Yunus; Muhamad Maulana Darsono; Mohamad Anton Athoillah (al-Afkar, Journal For Islamic Studies, 2023)
The purpose of this research is to analyze Akad Wakalah Bil Ujrah in the context of the preparation of Sharia Economic Law, fatwa and qanun and its impact on Islamic financial institutions. Akad Wakalah Bil Ujrah is a type of contract in Islamic finance law where one party acts as an agent to carry out transactions on behalf of another party for a fee. This study examines the rules and legal principles related to the Wakalah Bil Ujrah Agreement using the normative analysis method. The Compilation of Sharia Economic Law, Fatwa and Qanun are the main references to identify the rules governing this contract. In addition, the implementation of Wakalah Bil Ujrah in Islamic financial institutions is also analyzed using case studies of relevant Islamic financial institutions. The results of the study show that the Wakalah Bil Ujrah contract has a strong legal basis for compiling Islamic economic law, fatwa and qanun. Sharia principles are the main guidelines for the implementation of this contract, including the principles of justice, transparency and accountability. The impact on Islamic financial institutions includes investment management, pension fund management and sharia-based banking services. However, this study also identified several challenges in implementing Wakalah Bil Ujrah in Islamic financial institutions, such as the need for in-depth understanding of sharia principles and compliance with applicable regulations. Therefore, strict supervision and clear procedures are needed to ensure the fulfillment of sharia principles. In summary, Akad Wakalah Bil Ujrah plays an important role in the formulation of Sharia Economic law, Fatwas and Qanuns and has significant implications for Islamic financial institutions. To improve implementation, cooperation between Islamic financial institutions, regulators and academics should be enhanced to ensure compliance with Shariah principles and the achievement of sustainable financial goals.